Study on the Connection Between the Set Transient in RRAMs and the Progressive Breakdown of Thin Oxides - Aguirre, Fernando Leonel (2019)
In this paper, the transition rate (TR) from the high-resistance state to the low-resistance state of a HfO2-based resistive random access memory (RRAM) is investigated. The TR is statistically characterized by applying constant voltage stresses in the range from 0.45 to 0.65 V. It is found that TR follows a voltage dependence which closely resembles the one exhibited by metal-insulator-semiconductor / metal-insulator-metal structures when subjected to constant voltage stress, but with remarkably different fitting parameters. This result suggests a common underlying mechanism in both evolutionary behaviors. Furthermore, the investigation provides additional evidence supporting the micro-structural changes in the oxide after the forming step as well as the role played by the atomic species during the SET event.